Answer:
![f^(-1)(x)=(x)/(4) - 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zjdv1j4pjbw0kvwezsdlg7fn9covvwehsg.png)
Explanation:
the inverse function of the function f(x)=4x+8
To find inverse function do the following steps
step 1: Replace f(x) with y
y = 4x+8
step 2: Replace x with y and y with x
x= 4y +8
step 3: solve for y
x = 4y +8
Subtract 8 from both sides
x-8 = 4y
divide by 4 on both sides
![(x-8)/(4) = y](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qlz67touxk05d2w2gj8jibymi6h46ev6am.png)
Divide each term by 4
![y=(x)/(4) - 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/8075hcrvqln9z38gipn3txqieurhw5e3fy.png)
Step 4 : Replace y with f^-1(x)
![f^(-1)(x)=(x)/(4) - 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zjdv1j4pjbw0kvwezsdlg7fn9covvwehsg.png)